2008
DOI: 10.1515/hf.2008.114
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of total phenol contents of European oak (Quercus petraea and Quercus robur) by diffuse reflectance NIR spectroscopy on solid wood surfaces

Abstract: Near infrared spectroscopy (NIRS) combined with multivariate analysis techniques was applied to assess phenol content of European oak. NIRS data were firstly collected directly from solid heartwood surfaces: in doing so, the spectra were recorded separately from the longitudinal radial and the transverse section surfaces by diffuse reflectance. The spectral data were then pretreated by several pre-processing procedures, such as multiplicative scatter correction, first derivative, second derivative and standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
2
19
0
1
Order By: Relevance
“…Near infrared (NIR) spectroscopy, as a nondestructive detection and identification technology developed over the past 20 years, has the potential to meet these requirements. NIR spectroscopy has been widely used for the evaluation of wood density (Stirling et al 2007), wood grainangle (Gindl and Teischinger 2002), wood chemical composition (Zahri et al 2008), and veneer MOE (Meder et al 2002). It has also been applied in the detection of wood defects, such as discriminating blue-stained wood (Via et al 2006;Via et al 2008), distinguishing the type of fungal decay (Fackler et al 2007;Yang et al 2008), and detecting compression wood (Meder and Meglen 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Near infrared (NIR) spectroscopy, as a nondestructive detection and identification technology developed over the past 20 years, has the potential to meet these requirements. NIR spectroscopy has been widely used for the evaluation of wood density (Stirling et al 2007), wood grainangle (Gindl and Teischinger 2002), wood chemical composition (Zahri et al 2008), and veneer MOE (Meder et al 2002). It has also been applied in the detection of wood defects, such as discriminating blue-stained wood (Via et al 2006;Via et al 2008), distinguishing the type of fungal decay (Fackler et al 2007;Yang et al 2008), and detecting compression wood (Meder and Meglen 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors estimated the extractive contents of various woods (Terdwongworakul et al 2005 ;Tsuchikawa 2007 ;Zahri et al 2008 ;Schimleck et al 2009 ). Gierlinger et al (2002) showed that NIRS can substitute time-consuming conventional methods of analysis and is able to quickly predict the levels of total phenolics and extractives of the wood of Larix decidua , Larix leptolepis and a hybrid ( Larix x eurolepis ).…”
Section: Introductionmentioning
confidence: 99%
“…Reasonable predictions could be done with the models developed, especially in cases when the improved statistical techniques ( " kernel and wavelet " ) were applied. Zahri et al (2008) assessed quantitatively the total phenol contents of European oak by means of NIRS.…”
Section: Introductionmentioning
confidence: 99%
“…De Beer et al [19] compared several methods for the determination of the total phenol content; the Folin-Ciocalteu, RP-HPLC, and cyclic voltammetry results were found to be strongly correlated. Photoacoustic (PA) spectroscopy [20] in the ultraviolet and visible and near infrared spectroscopy (NIRS) combined with multivariate analysis techniques has also been proposed [21,22]. The usage of NMR spectroscopy in analytical chemistry bears inherent advantages, such as the observation of the compounds present in the sample in a single measurement and the minimal sample pretreatment.…”
Section: Introductionmentioning
confidence: 99%